Countering the Bomb Terror Threat by the Gegana Detachment of the Southeast Sulawesi Mobile Brigade Unit - Muhram, La Ode; Yusuf, Niken Yulian; Kurniawati, Wa Ode Intan; Supriadi, Supriadi; Hariru, La Ode; Zainuddin, Arief Rachman (International Journal of Management and Education in Human Development, 2023)
The era of reform has inspired a spirit of renewal, a spirit of repair, arrangement, and improvement which consciously highlights various inequalities, deviations, and disproportionate things. The separation of the National Police from the TNI is one of the agendas that occurred in the reform era, and it is a demand from the public who wants changes in the performance of the National Police in carrying out their duties, as stated in Article 13 of Law Number 2 of 2002 concerning the Police of the Republic of Indonesia, which states that: The main task of the National Police of the Republic of Indonesia is to maintain security and public order, enforce the law and provide protection, guidance and service to the community. One of the progress of the National Police that is worth noting as part of efforts to improve police performance since the separation from the TNI is the disclosure of bomb cases in Indonesia using the Scientific Crime Investigation (SCI) method, as a term that can be tested. For example, the disclosure of the Bali bombing case, which was initially doubted by many parties, regarding the ability of the National Police to uncover the case, even when the National Police were able to uncover the Bali bombing 1 step by step, unpleasant accusations were immediately heard, that the National Police had engineered the case. This type of research is included in the category of normative legal research. 2 factors, namely supporting factors and inhibiting factors. These factors are as follows:1. Supporting Factors 2. Inhibiting Factors. one of the suggestions given that the application of the Retroactive principle to cases of criminal acts of terrorism will not violate Human Rights because retroactivity is vulnerable to violations of Human Rights, however, the need for retroactive application is highly desirable, nowadays considering that the impact of criminal acts of terrorism is very broad and systemic.